Stunting in Indonesian Children and Its Contributing Factors: Study through Bibliometric Analysis - Bahrun; Wildan (Jurnal Pendidikan Usia Dini, 2022)
Children's stunting is a problem because it is associated with an increased risk of pain and death, suboptimal brain development resulting in late motor development, and inhibition of mental growth. This study aims to examine the factors that influence the occurrence of stunting and risk in children in Indonesia. The research method used is a traditional review. The results of the review found that many factors cause the high incidence of stunting in toddlers, including energy intake, birth weight, maternal knowledge level, family economic status, parental parenting, and food security. WHO estimates the prevalence of stunting worldwide at 22 percent or as many as 149.2 million in 2020. According to the Indonesian Nutritional Status Study (SSGI) results of the Ministry of Health, the prevalence of stunting in children under five in Indonesia reached 24.4% in 2021. The prevalence of stunting of toddlers in Indonesia continues to show a decline. In 2018 the prevalence of stunting toddlers was still 30.8%. Then, it dropped to 27.7 in 2019 and continued to fall to 24.4% in SSGI 2024. The government even targets to drop to 14% by the end of 2024. Furthermore, WHO also recommends reducing stunting by 3.9% per year to meet the target of 40% stunting reduction by 2025. Keywords: Indonesian children; stunting data; causes of stunting; the prevalence of stunting References: Aguayo, V. M., & Menon, P. (2016). Stop stunting: Improving child feeding, women’s nutrition and household sanitation in South Asia. Maternal and Child Nutrition, 12, 3–11. https://doi.org/10.1111/mcn.12283 Chaparro, C. (2017). FANTA-Guatemala-ENSMI-Report_March 2012. Creswell, J. W. (2014). Research Design: Qualitative, Quantitative and Mixed Methods Approaches (4th ed.). Thousand Oaks, CA: Sage. da Silva, I. C. M., França, G. V., Barros, A. J. D., Amouzou, A., Krasevec, J., & Victora, C. G. (2018). Socioeconomic inequalities persist despite declining stunting prevalence in low- and middle-income countries. Journal of Nutrition, 148(2), 254–258. https://doi.org/10.1093/jn/nxx050 de Onis, M., & Branca, F. (2016). Childhood stunting: a global perspective. Maternal & Child Nutrition, 12, 12–26. https://doi.org/10.1111/mcn.12231 Djauhari T. (2017). Gizi dan HPK 1000. Saintika Madika Effendy, F., Gaffar, V., Hurriyati, R., & Hendrayati, H. (2021). Analisis Bibliometrik Perkembangan Penelitian Penggunaan Pembayaran Seluler Dengan Vosviewer. Jurnal Interkom: Jurnal Publikasi Ilmiah Bidang Teknologi Informasi Dan Komunikasi, 16(1), 10–17. https://doi.org/10.35969/interkom.v16i1.92 Food and Agriculture Organization. (2008). Food Security Information for Action Practical Guides: An Introduction to the Basic Concepts of Food Security. Gibney MJ, Margetts BM, Kearney JM, Arab L. (2013). Gizi Kesehatan masyarakat. Probolinggo. EGC Fitroh, S. F., & Oktavianingsih, E. (2020). Peran Parenting dalam Meningkatkan Literasi Kesehatan Ibu terhadap Stunting di Bangkalan Madura. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 4(2), 610. https://doi.org/10.31004/obsesi.v4i2.415 Handayani, F., Siagian, A., & Aritonang, E. Y. (2017). Mother’s Education as A Determinant of Stunting among Children of Age 24 to 59 Months in North Sumatera Province of Indonesia. IOSR Journal of Humanities and Social Science, 22(06), 58–64. https://doi.org/10.9790/0837-2206095864 Humphrey, J. H., Mbuya, M. N. N., Ntozini, R., Moulton, L. H., Stoltzfus, R. J., Tavengwa, N. V., Mutasa, K., Majo, F., Mutasa, B., Mangwadu, G., Chasokela, C. M., Chigumira, A., Chasekwa, B., Smith, L. E., Tielsch, J. M., Jones, A. D., Manges, A. R., Maluccio, J. A., Prendergast, A. J., … Makoni, T. (2019). Independent and combined effects of improved water, sanitation, and hygiene, and improved complementary feeding, on child stunting and anaemia in rural Zimbabwe: a cluster-randomised trial. The Lancet Global Health, 7(1), e132–e147. https://doi.org/10.1016/S2214-109X(18)30374-7 Ikeda, N., Irie, Y., & Shibuya, K. (2013). Determinants of reduced child stunting in Cambodia: analysis of pooled data from three Demographic and Health Surveys. Bulletin of the World Health Organization, 91(5), 341–349. https://doi.org/10.2471/blt.12.113381 Kemenkes RI. (2013). Badan Penelitian dan Pengembangan Kesehatan. Riset Kesehatan Dasar Kemenkes RI. (2018). Buku Saku Pemantauan Status Gizi Tahun 2017. Direktorat Jenderal Kesehatan Masyarakat. Kemenkes RI (2021) ‘Buku Saku Hasil Studi Status Gizi Indonesia (SSGI) tingkatnasional, provinsi, dan kabupaten/kota tahun 2021’, Angewandte Chemie International Edition, 6(11), 951–952., pp. 2013–2015 Kementerian Desa, Pembangunan Daerah Tertinggal, dan T. (2017). Buku saku desa dalam penanganan stunting. In Buku Saku Desa Dalam Penanganan Stunting. Jakarta: Kementrian Desa, Pembangunan Daerah Tertinggal, dan Transmigrasi Leroy, J. L., & Frongillo, E. A. (2019). Perspective: What Does Stunting Really Mean? A Critical Review of the Evidence. In Advances in Nutrition (Vol. 10, Issue 2, pp. 196–204). Oxford University Press. https://doi.org/10.1093/advances/nmy101 Martha, E., Nadira, N. A., Sudiarti, T., Mayangsari, A. P., Ferdina Enjaini, E., Ryanthi, T. P., Evariyana Bangun, D., Prof, J., & Djohan, B. (2020). THE EMPOWERMENT OF CADRES AND MEDICASTERS IN THE EARLY DETECTION AND PREVENTION OF STUNTING. https://doi.org/10.20473/ijph.vl15il.2020.153-161 Muche, A., Gezie, L.D., Baraki, A.G.-E., & Amsalu, E. T. (2021). Predictors of stunting among children age 6 – 59 months in Ethiopia using Bayesian multi-level analysis. Scientific Reports, 11(1), 3759: https://doi.org/10.1038/s41598-021-82755-7 Musheiguza, E., Mahande, M. J., Malamala, E., Msuya, S. E., Charles, F., Philemon, R., & Mgongo, M. (2021). Inequalities in stunting among under-five children in tanzania: Decomposing the concentration indexes using demographic health surveys from 2004/5 to 2015/6. International Journal for Equity in Health, 20(1). https://doi.org/doi:10.1186/s12939-021-01389-3 Nugroho, M. R., Sasongko, R. N., & Kristiawan, M. (2021). Faktor-faktor yang Mempengaruhi Kejadian Stunting pada Anak Usia Dini di Indonesia. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(2). https://doi.org/10.31004/obsesi.v5i2.1169 Oswari H, Djer MM, Dewi R, Harijadi. (2016) . Kiat membuat anak sehat, tinggi, dan cerdas. Ikatan Dokter Anak Indonesia Cabang DKI Jakarta: Jakarta Ohyver, M., Moniaga, J. V., Yunidwi, K. R., & Setiawan, M. I. (2017). Logistic Regression and Growth Charts to Determine Children Nutritional and Stunting Status: A Review. Procedia Computer Science, 116, 232–241. https://doi.org/10.1016/j.procs.2017.10.045 Paudel, R. (2012). Risk Factors for Stunting Among Children: A Community Based Case Control Study in Nepal. In Kathmandu Univ Med J (Vol. 39, Issue 3). Rahayu, A., Yulidasari, F., Putri, A. O., & Rahman, F. (2015). Riwayat Berat Badan Lahir dengan Kejadian Stunting pada Anak Usia Bawah Dua Tahun. Kesmas: National Public Health Journal, 10(2), 67. https://doi.org/10.21109/kesmas.v10i2.882 Rahmadhita, K. (2020). Jurnal Ilmiah Kesehatan Sandi Husada Permasalahan Stunting dan Pencegahannya Pendahuluan. Jurnal Ilmiah Kesehatan Sandi Husada, 11(1), 225–229. https://doi.org/10.35816/jiskh.v10i2.253 Ramadhan, R., & Ramadhan, N. (2018). Determinasi Penyebab Stunting Di Provinsi Aceh Determination of Stunting Causes in Aceh Province. SEL Jurnal Penelitian Kesehatan, 5(2), 71–79. Riyadi, H., Martianto, D., Hastuti, D., Damayanthi, E., & Murtilaksono, K. (2011). Faktor-Faktor Yang Mempengaruhi Status Gizi Anak Balita Di Kabupaten Timor Tengah Utara, Provinsi Nusa Tenggara Timur. Jurnal Gizi Dan Pangan, 6(1), 66. https://doi.org/10.25182/jgp.2011.6.1.66-73 Rosha, B. C., Sari, K., SP, I. Y., Amaliah, N., & Utami, N. H. (2016). Peran Intervensi Gizi Spesifik dan Sensitif dalam Perbaikan Masalah Gizi Balita di Kota Bogor. Buletin Penelitian Kesehatan, 44(2). https://doi.org/10.22435/bpk.v44i2.5456.127-138 Safitri, C. A., & Nindya, T. S. (2017). Relations food security and diarrheal disease to stunting in under-five children age 13-48 months at Manyar Sabrangan, Mulyorejo Sub-District, Surabaya. Amerta Nutrition, 1(2), 52–61. https://doi.org/10.2473/amnt.v1i2.2017.52-61 Sari, M. R. N., & Yusi Ratnawati, L. (2018). Hubungan Pengetahuan Ibu tentang Pola Pemberian Makan dengan Status Gizi Balita di Wilayah Kerja Puskesmas Gapura Kabupaten Sumenep Relation Between Mothers’ Knowledge About Feeding Method and Toddlers’ Nutritional Status in the Working Area of Puskesmas. Amerta Nutr, 2(2), 30–36. https://doi.org/10.2473/amnt.v2i2.2018.182-188 Sekretariat Wakil Presiden Republik Indonesia. (2021). Capaian, Tantangan Dan Peluang Pelaksanaan Strategi Nasional Percepatan Pencegahan Stunting Tahun 2018 – 2024. Jakarta: Sekretariat Wakil Presiden Republik Indonesia Setiawan, E., & Machmud, R. (2018). Faktor-Faktor yang Berhubungan dengan Kejadian Stunting pada Anak Usia 24-59 Bulan di Wilayah Kerja Puskesmas Andalas Kecamatan Padang Timur Kota Padang Tahun 2018. In Jurnal Kesehatan Andalas (Vol. 7, Issue 2). http://jurnal.fk.unand.ac.id Stewart, C. P., Iannotti, L., Dewey, K. G., Michaelsen, K. F., & Onyango, A. W. (2013). Contextualising complementary feeding in a broader framework for stunting prevention. Maternal and Child Nutrition, 9(S2), 27–45. https://doi.org/10.1111/mcn.12088 Sustainable, T., & Goals, D. (2016). The sustainable development goals report 2016. The Sustainable Development Goals Report 2016. https://doi.org/10.29171/azu_acku_pamphlet_k3240_s878_2016 Sutarto, Mayasari, D., & Indriyani, R. (2018). Stunting, Faktor Resiko dan Pencegahannya. Jounal Agromedicine, 5, 540–545. https://doi.org/10.1201/9781439810590-c34 Ulfah, E., Rahayuningsih, S. E., Herman, H., Susiarno, H., Gurnida, D. A., Gamayani, U., Sukandar, H., Studi, P., Kebidanan, M., Ilmu, D., Anak, K., Orthopaedi, D., Traumatologi, D., Obstetri Dan Ginekologi, D., Neurologi, D., & Epidemiologi, D. (2018). ARTIKEL PENELITIAN Global Medical and Health Communication Asuhan Nutrisi dan Stimulasi dengan Status Pertumbuhan dan Perkembangan Balita Usia 12-36 Bulan. https://doi.org/10.29313/gmhc.v6i1.2323 UNICEF. (2013). Improving Child Nutrition : The Achievable Imperative for Global Progress. UNICEF, W. T. (2019). Levels and Trends in child malnutrition - UNICEF WHO The World Bank Join Child Malnutrition Estmates WHO. (2010). Indicator For Assesing And Young Child Feeding Practices Part 2 : Measurement. WHO Press. World Health Organization. (2014). Global Nutrition Targets 2025: Stunting Policy Brief (No.WHO/NMH/NHD/14.3) Zogara, A. U., & Pantaleon, M. G. (2020). Faktor-faktor yang Berhubungan dengan Kejadian Stunting pada Balita. Jurnal Ilmu Kesehatan Masyarakat, 9(02), 85–92. https://doi.org/10.33221/jikm.v9i02.505